Freeze-thaw performance of prestressed concrete railroad ties - Albahttiti, Mohammed T. (Kansas State University, 2015)
Air voids are purposefully entrained in concrete to provide freeze-thaw durability of prestressed concrete railroad ties. Durability assurance requires consistent provision of an air void system comprised of small, well-distributed bubbles in sufficient quantity for durability and a quality control method for testing tie freeze-thaw durability. Manufacturing processes at three concrete manufacturing plants were investigated in order to determine the effects of process variability on resulting concrete air void system variability. Variation in the concrete air void system and other rheological properties occurred as results of the manufacturing process and vibration. Freezing and thawing durability testing of prestressed concrete ties is currently performed by applying ASTM C666 on 3 x 4 x 11 to 16 in. specimens cut from the shoulders of concrete ties. However, excising these specimens from prestressed concrete could lead to stress changes in the sample and cracking, potentially causing false interpretations of results. Therefore, testing was undertaken to understand the effects of prestressing and sample extraction on freeze-thaw durability measured by ASTM C666. In order to assess the effects of sampling and testing procedures on freeze-thaw quality control testing results of prestressed concrete railroad ties, full ties, half ties, and 3 x 4 x 11 in. excised samples were tested. Freeze-thaw testing included determination of the optimal method to measure freeze-thaw deterioration in large sections, the effects of saw-cutting, and the presence of reinforcement. Results indicated that the Ultrasonic Pulse Velocity accurately represented deterioration in large sections. The presence of reinforcement in excised samples led to faster deterioration compared to cast ASTM C666 samples, while saw-cutting without reinforcement did not significantly affect freeze-thaw durability.
Keywords: Railroad ties; Freeze-thaw durability; Air void system; Concrete vibration; Prestressed concrete durability; Bursting strains; Civil Engineering (0543)